2012
DOI: 10.1289/ehp.1103884
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Birth Outcomes and Maternal Exposure to Trichloroethylene and Tetrachloroethylene through Soil Vapor Intrusion in New York State

Abstract: Background: Industrial spills of volatile organic compounds (VOCs) in Endicott, New York (USA), have led to contamination of groundwater, soil, and soil gas. Previous studies have reported an increase in adverse birth outcomes among women exposed to VOCs in drinking water.Objective: We investigated the prevalence of adverse birth outcomes among mothers exposed to trichloroethylene (TCE) and tetrachloroethylene [or perchloroethylene (PCE)] in indoor air contaminated through soil vapor intrusion.Methods: We exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
104
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 17 publications
2
104
0
Order By: Relevance
“…The occurrence of CVOCs in groundwater systems poses a serious environmental threat to both natural ecosystem integrity and human water uses (Lapworth et al, 2012; Anaya et al, 2013). Exposure to CVOCs is potentially harmful to human health and may contribute to adverse reproductive outcomes (Sonenfeld et al, 2001; Forand et al, 2012), as well as damage to the nervous system (Bale et al 2011), liver and kidney (Lash et al, 2000), immune system (Cooper et al, 2009) and lungs (Odum et al, 1992; Chiu et al, 2013). CVOCs typically have long residence times (hundreds to thousands of years) in groundwater due to their low solubility, persistence in the environment due to low degradation rates, and immobility (Heron et al, 2009; Liu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of CVOCs in groundwater systems poses a serious environmental threat to both natural ecosystem integrity and human water uses (Lapworth et al, 2012; Anaya et al, 2013). Exposure to CVOCs is potentially harmful to human health and may contribute to adverse reproductive outcomes (Sonenfeld et al, 2001; Forand et al, 2012), as well as damage to the nervous system (Bale et al 2011), liver and kidney (Lash et al, 2000), immune system (Cooper et al, 2009) and lungs (Odum et al, 1992; Chiu et al, 2013). CVOCs typically have long residence times (hundreds to thousands of years) in groundwater due to their low solubility, persistence in the environment due to low degradation rates, and immobility (Heron et al, 2009; Liu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…10 For example, it was recently reported that maternal exposure to trichloroethylene and perchloroethylene is associated with adverse birth outcomes. 11 Residential exposure to VOCs has been linked to respiratory symptoms 12,13 and to asthma in young children in particular. 14 Globally, there is a continued interest in studying the levels of VOCs in indoor environments due to their potential health effects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…pdf; Forand et al, 2012). A more recent analysis of the same region of New York State found that maternal residence in an area contaminated with TCE or PCE was associated with cardiac birth effects, but these effects were only significant for the TCE-exposed group (Forand et al, 2012). In contrast, a study in Texas found weak to no evidence of an association between TCE or PCE exposure and developmental cardiotoxicity (Brender et al, 2014).…”
Section: Noncancer Toxicitymentioning
confidence: 99%
“…gov/hac/pha//endicottareainvestigationfollowup/endicottareahc051508. pdf; Forand et al, 2012). A more recent analysis of the same region of New York State found that maternal residence in an area contaminated with TCE or PCE was associated with cardiac birth effects, but these effects were only significant for the TCE-exposed group (Forand et al, 2012).…”
Section: Noncancer Toxicitymentioning
confidence: 99%